A pilot study examining the impact of collaborative mind mapping strategy in a flipped classroom: learning achievement, self-efficacy, motivation, and students’ acceptance - Zheng, Xudong; Johnson, Tristan E.; Zhou, Chunhong (Educational technology research and development, 2020)
Appropriate collaborative learning support is necessary for group learning in a flipped classroom setting, especially in the out-of-class learning phase. This study involved a collaborative mind mapping strategy to engage learners in group activities in the flipped classroom setting. A pilot experiment was conducted to examine the effect of such a strategy on students’ learning achievement, self-efficacy, motivation, and acceptance of mind mapping in a news photography course. Specifically, this study compared the effects of two mind mapping strategies (collaborative vs. individual) combined with instructional methods (flipped classroom vs. conventional) on students’ learning outcomes. A 2 × 2 mixed-factorial experiment design was used, with the mind mapping strategies as the within-subjects factors and the instructional methods as the between-subjects factors. Ninety-two sophomores enrolled in this course were randomly assigned to either flipped classroom or conventional lecturing. Both method groups used collaborative and individual mind mapping. Results revealed that the combination of a collaborative mind mapping strategy and a flipped classroom significantly improved students’ learning achievement and self-efficacy. In addition, flipped classroom students had a more positive attitude toward accepting and using collaborative mind mapping than those in the individual mind mapping condition. These implications provided instructional designers guidance to apply collaborative mind mapping into a flipped classroom and suggested that designers should focus on improving students’ motivation by integrating other strategies.